Analisis Keputusan Berkunjung Siswa ke Museum Kelahiran Bung Hatta di Kota Bukittinggi - Anisa Putri Afra (Institut Seni Indonesia Padangpanjang, 2026)
This study aims to analyze studentsâ€™ visiting decisions to the Bung Hatta Birthplace Museum in Bukittinggi as an educational tourism destination. The research uses a quantitative descriptive method with data collected through questionnaires distributed to 100 respondents selected using purposive sampling. Data analysis was conducted using descriptive analysis with the Respondent Achievement Level (TCR) based on a Likert scale. The results show that studentsâ€™ visiting decisions fall into the â€œfairly goodâ€ category, with TCR values ranging from 75% to 82% across indicators such as place and time selection, readiness of time and cost, personal decision, realization of visits, and educational value and experience. These findings indicate that the museum has potential as an educational tourism destination for students, although improvements are still needed in facilities, educational programs, and promotion.